APLIKASI METODE DEKOMPOSISI ADOMIAN UNTUK MENENTUKAN FORMULA TRANSFORMASI LAPLACE - Aji Wiratama; Yuni Yulida; Thresye Thresye (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2014)
In this paper we will discuss about Laplace transformation formation from solution of first order linear differential equation. One of the approaches to the solution of first-order linear differential equations can apply the Adomian decomposition method. The solution is written in an infinite series. Further, the solution uses the Adomian decomposition method and the exact solution obtained by the integration factor compared to the Laplace transform formula.